Implementation of evaluation on policies and programs in the Malaysian public sector: an empirical examination of antecedents and consequences / Rafidah Mohamed Hashim - Mohamed Hashim, Rafidah (2020)
Evaluation has become synonymous when it comes to measuring the performance of policies and programs. The present study aimed to investigate the antecedents and consequences of evaluation implementation on policies and programs at the ministry level in the Malaysian public sector. It provided a comprehensive understanding of the evaluation capacity building (ECB) factors that facilitate the implementation of evaluation activities as well as the consequences, which are rarely studied in one comprehensive framework. By using the stratified sampling technique, 372 questionnaires were distributed at 24 ministries, yielded 340 returned questionnaires with only 295 fit for the final data analysis. The study applied both the Statistical Package for Social Sciences (SPSS) and the SmartPLS for data analysis. The final structural model brought a result of nine hypotheses were proven significant with the scores of t-values between 2.121 to 7.169 well above the minimum cut-off value of 1.645 for an alpha level of 0.05. As for the evaluation use, only evaluation regulatory framework and financial resources with t-values of 2.834 and 2.229, were found significant towards accountability and organisational learning, respectively. Meanwhile, evaluation office and internal evaluators with t-values scores of 0.874 and 1.177 were found not important in the relationships. The level of each variable except financial resources, was found at the low point across all ministries, indicating urgent attention and action to be taken by the top management. While previous studies offered a relatively vague understanding of ECB, this study added a new perspective at looking at ECB factors from the structural lenses. In examining the relationships, this study introduced two new variables; evaluation office and evaluation regulatory framework as unique and vital factors from the structural perspective along with new set of items derived with acceptable Cronbach’s alpha scores of 0.862 and 0.846, respectively. This study contributed to enriching the ‘coercive isomorphism’ aspect of the institutional theory by adding the importance of internal pressure in organisations apart from the external pressure. The element of ‘regulatory’ instead of rigid acts or laws was found important in evaluation work in the developing country setting. Based on the results, the study concluded that all ECB factors significantly influenced the implementation of evaluation activities at the ministry level. This information is critical for leaders in the public sector in efforts to prepare an environment conducive for evaluation work to grow. In the end, this study presented a statistically significant, unified, and integrated framework that became a meaningful contribution to the existing knowledge in the evaluation field.